Internet of Things Based Devices Designed for Pediatric Therapy to Improve Mobility and Engagement in Children with Cerebral Palsy - AbouGhaly, Mahmoud; Akhtar, Nikhat; Ahmed, Elturabi Osman; Kumar, Sunny; Perwej, Yusuf; Tamma, Ratna Kumari (Journal of Neonatal Surgery, 2025)
The subjects of the paper are the creation and seeing of an Internet of Things (IoT) based equipment focused to enhance. These limitations translate to exciting opportunities for innovation, despite previous reports pointing out issues like sample size, adaptability of the systems to other tasks, and high require- ments on computational resources. To ensure the balance between comfort, durability and scalability, this research aims to provide a highly customisable IoT solution that can be used both in clinical and home environments It uses a combination of live data feeds, individual therapy modifications and machine learning models to improve the therapeutic experience for children with different degrees of cerebral palsy severity. Additionally, the emphasis on creating inexpensive, easy-to-use devices will make these visits possible in places with limited resources. The research described in this article is a step towards a tailored IoT-based solution for pediatric rehabilitation, bridging current gaps in the literature and offering a solution with a broader design in therapy considering the wide range of rehabilitative health profiles.